Rape & zina: a comparative study between the Islamic penal law and the penal code of Malaysia / Ismail Said - Said, Ismail (Faculty of Law, 1984)
This project paper is on the subject of a comparative study of the offences of rape and zina. In chapter one the writer deals extensively on the substantive law of rape. Subsequently in chapter two the writer deals with the substantive law of zina. Alongside the writer also discuss the differences and similarities of both offences. In chapter three the study is solely on the penalties of bothoffenc.es. This covers the theoritical and practical aspect. Further it is necessary to discuss the problems as regards the application of the Islamic law in Malaysia. Unlike the penal code which is a code of general application. There is no impediment to it's application. With this in mind the writer has dedicated chapter four to this aspect; Problems of Application. Ultimately the writer tried to present this paper with much details as possible with the limited sources available and other unavoidable limitations. For whatever error remains, then, the writer is solely responsible.